If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1(-5 + 4i) + -1(-13 + -1) = 0 6 + (-5 * -1 + 4i * -1) + -1(-13 + -1) = 0 6 + (5 + -4i) + -1(-13 + -1) = 0 Combine like terms: -13 + -1 = -14 6 + 5 + -4i + -1(-14) = 0 Multiply -1 * -14 6 + 5 + -4i + 14 = 0 Reorder the terms: 6 + 5 + 14 + -4i = 0 Combine like terms: 6 + 5 = 11 11 + 14 + -4i = 0 Combine like terms: 11 + 14 = 25 25 + -4i = 0 Solving 25 + -4i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + -4i = 0 + -25 Combine like terms: 25 + -25 = 0 0 + -4i = 0 + -25 -4i = 0 + -25 Combine like terms: 0 + -25 = -25 -4i = -25 Divide each side by '-4'. i = 6.25 Simplifying i = 6.25
| 2s^2=7s+4 | | 2x+1-2x=12 | | 4x+7=14+4x | | Z^2+3z+28=-12 | | 69.1=2(3.14)r | | X=-7x | | 4.5m=67.5 | | 169-78x+9x= | | a+2a+4a=56 | | 31-g+14+2g=21 | | -5--2x=-45 | | f(x)=2(3) | | 90.48=-5.8(v-7.6) | | 4x+2y=-6z | | 11-2m=14+3m | | (-4y^2-6y)+(5y^2+2y-5)= | | g(3)=x^2-3x | | 5x-2+2x=5x+x+7 | | 2a+2a+2a=56 | | 6n-10=2n+18 | | 146=l(20) | | (.5*x)*x=162 | | x-91=-7x+37 | | 0.15y=0.24 | | -3+4n=6n+3 | | 3z+20whenz=-8 | | 0.15=0.24 | | 156+125=180 | | .5x*x=162 | | 13x+1=y | | 0.5+3+125=180 | | 200=.5(10+x)4 |